Biometric Voting System - Prasad Ramchandra Mavarkar; Jaychandra C; Vrashabh Naik; Krishna Talli; Shivanad Uttur; Parvati Nayak; Lakshmi Bhasme (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
A biometric voting system abstract would outline the key features and principles of a voting system that utilizes biometric authentication methods, such as fingerprint or iris recognition, to ensure secure and accurate voter identification. It would emphasize the system's potential to enhance the integrity of elections by reducing fraud and ensuring each voter's unique identity. Additionally, the abstract might touch upon the technological aspects, security measures, and potential challenges associated with implementing a biometric voting system. The model proposed enables the voter to poll his vote in any of the polling station in his state or anywhere in the country. The voting terminals may be interconnected using IOT technology.
Keywords: Biometric Authentication; Iris Scanning; Fingerprint Recognition; Voter Identification; Election Integrity; Secure Voting; Fraud Prevention; Biometric Data Encryption; Voter Privacy; Technology Implementation; Electoral System; Authentication Accuracy; Voter Registration; Authentication Protocols; Election Security